Space utilization of the physical environment of a selected BPO office decompression spaces and its relation to the productivity and well-being of call center agents - Santos, Leslie S. Calubayan
Business Process Outsourcing (BPO) is an ever-growing industry that has been one of the biggest contributors to employment and economic progression worldwide. The Filipinos have shown interest in this industry due to the promise of higher compensation. BPOs have been the topic of more academic research due to the operation’s complexity and employment size. Still, only a few studies have focused on the physical environment of decompression or shared spaces and the agents' utilization relating to their workplace well-being and level of productivity. This study thoroughly analyzed how physical space utilization, specifically decompression or shared spaces, impacts the productivity and workplace well-being of call center agents. To achieve this, the researcher employed a descriptive research approach that integrates a mixed-methods strategy for data collection, employing physical environment observation and survey questionnaires. A total of 110 participants were purposively selected from a prominent BPO company located in Quezon City. The participants were selected based on their frequency of utilization of the determined decompression or shared spaces, then categorized into two clusters: frequent users and non-frequent users. The research framework was patterned on the Affective Events Theory (AET), which explains how the workplace environment and events may affect employee behavior, workplace attitude, which would lead to productivity and well-being. The findings indicated a significant correlation between the frequency with which employees utilized decompression spaces and their overall workplace well-being, as well as their productivity levels. The findings in this research suggest that the variables of the physical environment of decompression or shared spaces can enhance the work experience of call center agents, that would eventually lead to productivity and workplace well-being.